Effects of caffeine and carbohydrate on time trial cycling - Rehre, N. J.; Cusdin, T.; Deutsch, M. (Medicine & Science in Sports & Exercise, 1997)
The effects of caffeine with and without carbohydrate supplementation on blood glucose and a 30-minute cycling time trial were investigated. Trained male cyclists (N = 15) performed four trials: caffeine plus carbohydrate, placebo plus carbohydrate, caffeine plus aspartame water, and placebo plus water. Both caffeine and carbohydrate influenced blood glucose but did not affect the 30-minute cycling performance. Implication. Although blood glucose levels are altered by their supplementation, neither carbohydrate nor caffeine improved performance in a 30-minute cycling time trial.